Effect of Self-Referral on Bone Mineral Density Testing and Osteoporosis Treatment - Warriner, Amy H. (2014)
BACKGROUND: Despite national guidelines recommending bone mineral density screening with dual-energy xray absorptiometry (DXA) in women ≥65 years old, many women do not receive initial screening. OBJECTIVE: To determine the effectiveness of health system and patient-level interventions designed to increase appropriate DXA testing and osteoporosis treatment through (1) an invitation to self-refer for DXA (self-referral), (2) self-referral plus patient educational materials, and (3) usual care (UC, physician referral). RESEARCH DESIGN: Parallel, group-randomized, controlled trials performed at Kaiser Permanente Northwest (KPNW) and Kaiser Permanente Georgia (KPG). SUBJECTS: Women ≥ 65 years old without a DXA in past 5 years. MEASURES: DXA completion rates 90 days after intervention mailing and osteoporosis medication receipt 180 days after initial intervention mailing. RESULTS: From >12,000 eligible women, those randomized to self-referral were significantly more likely to receive a DXA than UC (13.0 – 24.1% self-referral vs. 4.9 – 5.9% UC, p < 0.05). DXA rates did not significantly increase with patient educational materials. Osteoporosis was detected in a greater proportion of self-referral women compared to UC (p < 0.001). The number needed to receive an invitation to result in a DXA in KPNW and KPG regions was approximately 5 and 12, respectively. New osteoporosis prescription rates were low (0.8 – 3.4%) but significantly greater among self-referral versus UC in KPNW. CONCLUSIONS: DXA rates significantly improved with a mailed invitation to schedule a scan without physician referral. Providing women the opportunity to self-refer may be an effective, low-cost strategy to increase access for recommended osteoporosis screening.